شعرية الرمز في ديوان "سأخرج من صورتي ذات يوم" لسميح القاسم - شعبان, سعيدة; بن داود, حدى; هميسي, رونق (جامعة الوادي - University of Eloued, 2023)
الملخص: • إن الشعرية عند العرب والغرب تختلف بحسب اتجاهات الدارسين لها. • إن الرمز وسيلة من وسائل التعبير وتكثيف المعنى وتعمقه إذ يجعل القارئ يعيش خيال القصيدة حتى يجد نفسه منغمسا في عالم التفكير والتدبر والتي سمحت لسميح القاسم بأن يفضي عما بداخله والتعبير عن أحاسيسه. • لخص الشاعر سميح القاسم تجربته الذاتية والإنسانية في الرمز بطريقة ابداعية فيها تكثيف وتفاعل وتركيز مع هذه الرموز وهي :الرمز التاريخي والديني والطبيعي والأدبي والأسطوري ,وذلك لسعة إطلاعه على الثقافات المختلفة في شتى المجالات. • استخدم الشاعر الرموز الطبيعية كالموت والليل اللذان شكلا حضورا قويا وذلك نتيجة الظروف العامة والخاصة التي مر بها. • تعتبر التجربة الشعرية عند سميح القاسم من أعمق وأصدق التجارب العربية التي تصور وتجسد هموم الانسان في بلده خاصة والبلدان العربية والإسلامية عامة. Abstract • The poetics of the Arabs and the West differ according to the attitudes of its scholars. • The symbol is a means of expression and the intensification and deepening of the meaning, as it makes the reader live the imagination of the poem until he finds himself immersed in the world of thinking and contemplation, which allowed Samih Al-Qasim to reveal what is inside him and express his feelings. • The poet Samih Al-Qasim summed up his personal and human experience in the symbol in a creative way in which there is intensification, interaction and focus with these symbols, namely: the historical, religious, natural, literary and mythical symbol, due to his wide knowledge of different cultures in various fields. • The poet used natural symbols such as death and night, which formed a strong presence, as a result of the general and special circumstances he went through. • The poetic experience of Samih Al-Qasim is considered one of the deepest and most sincere Arab experiences that depict and embody human concerns in his country in particular and the Arab and Islamic countries in general..
Keywords: عربيّــة: شعرية - الرمز - ديوان "سأخرج من صورتي ذات يوم" - سميح القاسم.; Poetry - Symbol - Diwan "I will get out of my image one day" - Samih Al-Qasim.